The Moral Philosophy of Capitalism In the View of the Javanese Islamic Trade Ethos - Daryono Daryono; Suparman Syukur (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2020)
The results of this paper were based on library research which aimed to understand capitalism in terms of Javanese Muslim trade ethos based on the work of experts. On the one hand, there was a mismatch between the economic system of capitalism and the ethos for the objectification of Islam in commerce and the results were suitable for world views and cultural life. Java was in a postcolonial state on the other hand. The method of analyzing its understanding was through historical and normative social as well as normative ethics and metaethics. The analysis resulted in three characteristics of the theoretical construction of Javanese Muslim trade ethos as a way of being kind, namely respect and care for anything, respect and harmony or care for anyone and in accordance with the culture and religious experience of Javanese Muslims at that time. These three characteristics had been proven during the Mangkunegara IV period, capable of creating human progress in various fields of life, especially the Mangkunegaran kingdom, for example, it was called Kala Sumbaga (a prosperous period). Therefore, this theoretical construction was expected to be an alternative to ethical thinking and vision in trade at the regional or national level.